Breast cancer in low-resource settings: Prioritizing the awareness and access programmes to overcome sociocultural and economic barriers for early detection and improved outcomes - Iqbal, Mohammad Shamim; Hossain, Mohammad Sorowar; Niessen, Louis (© 2014 Lippincott Williams and Wilkins, 2017)
This letter was published in the European Journal of Cancer Prevention [ © 2014 Lippincott Williams and Wilkins ] and the definite version is available at: http://dx.doi.org/10.1097/CEJ.0000000000000043 The Journal's website is at: http://journals.lww.com/eurjcancerprev/Citation/2014/07000/Breast_cancer_in_low_resource_settings__.8.aspx